2005
DOI: 10.4049/jimmunol.174.5.3059
|View full text |Cite
|
Sign up to set email alerts
|

Processing of C3b-Opsonized Immune Complexes Bound to Non-Complement Receptor 1 (CR1) Sites on Red Cells: Phagocytosis, Transfer, and Associations with CR1

Abstract: Severe anemia is a lethal complication of Plasmodium falciparum malaria, particularly in children. Recent studies in children with severe P. falciparum anemia have demonstrated elevated levels of E-bound Abs, reduced E-associated complement receptor 1 (CR1) and decay-accelerating factor (DAF), and pronounced splenic enlargement, suggesting a mechanism for E loss involving Abs, complement, and phagocytosis. Motivated by these reports, we have developed an in vitro model in which human E with Abs and complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…During childhood malarial anemia, the erythrocytes remaining in the circulation have reduced levels of two key complement proteins: CR1, the immune adherence receptor for C3b, and CD55, a complement control protein that down-regulates deposition of C3b on cells (12,20,22). Moreover, several reports, based on in vitro investigations and clinical observations, have revealed that complement-activation products, in particular C3b and its fragments, can be found on erythrocytes in the bloodstream during many phases of malaria infections (23)(24)(25), and our in vitro studies have demonstrated loss of CD55 upon chelation with anti-CD55 mAbs followed by interaction with model monocyte/macrophages (26). In view of the fact that free hematin can activate complement (27), and because hematin is known to bind to erythrocytes (5,6,21), we have examined the hypothesis that activation of complement, promoted by the binding of hematin to uE in the bloodstream, may play an important role in the pathogenesis of malarial anemia and the destruction of uE.…”
supporting
confidence: 55%
“…During childhood malarial anemia, the erythrocytes remaining in the circulation have reduced levels of two key complement proteins: CR1, the immune adherence receptor for C3b, and CD55, a complement control protein that down-regulates deposition of C3b on cells (12,20,22). Moreover, several reports, based on in vitro investigations and clinical observations, have revealed that complement-activation products, in particular C3b and its fragments, can be found on erythrocytes in the bloodstream during many phases of malaria infections (23)(24)(25), and our in vitro studies have demonstrated loss of CD55 upon chelation with anti-CD55 mAbs followed by interaction with model monocyte/macrophages (26). In view of the fact that free hematin can activate complement (27), and because hematin is known to bind to erythrocytes (5,6,21), we have examined the hypothesis that activation of complement, promoted by the binding of hematin to uE in the bloodstream, may play an important role in the pathogenesis of malarial anemia and the destruction of uE.…”
supporting
confidence: 55%
“…In vitro, oligomers of GPA are known to form when IgM cold-reacting antibodies trigger complement activation (33). Other membrane proteins may also be affected when C3b is deposited; for example, Craig et al reported an altered distribution of complement receptor 1 (CR1) in the rbc membrane (34). Together, the SPT and tetherpulling results suggest that the effect of a relatively small number of C3b molecules on GPA and band 3 mobility is amplified by another mechanism.…”
Section: Figurementioning
confidence: 99%
“…12 Complement C3 activation has clinical implications for extravascular hemolysis because it causes increased macrophage-mediated phagocytosis. 28 Hemolysis following ABO-mismatched platelet transfusions is uncommon, with a clinical incidence of ;0.01%. 16,29 However, it is becoming increasingly clear that persistent hemolysis may be clinically relevant in terms of organ failure, thrombosis, and mortality.…”
Section: Discussionmentioning
confidence: 99%